Creative Leadership and its Impact on Achieving Institutional Happiness at King Abdulaziz University (The International Journal of Educational Sciences and Arts, 2025)
The study aimed to explore the extent to which department heads and female supervisors of academic departments practice creative leadership from the perspective of faculty members, as well as to identify the level of institutional happiness at King Abdulaziz University from the faculty's point of view. Additionally, it examined the correlation between the practice of creative leadership and the level of institutional happiness among faculty members, and the impact of creative leadership on achieving institutional happiness at King Abdulaziz University. The study adopted a descriptive correlational methodology and included a sample of 348 faculty members. A questionnaire was used as the primary tool for data collection. The findings revealed that department heads and female supervisors practice creative leadership to a high degree. The results also indicated that the level of institutional happiness among faculty members was moderate. Furthermore, a statistically significant positive correlation was found between the degree of creative leadership practiced by department heads and supervisors and the level of institutional happiness from the perspective of faculty members. Based on the results, the study recommended enhancing leadership development programs to improve creative leadership skills across all university faculties. It also emphasized the importance of developing clear plans aimed at achieving institutional happiness for all university affiliates, thereby strengthening the sense of belonging and institutional commitment.
Keywords: Creative Leadership; Institutional Happiness; Fluency; Flexibility; Originality